2020
DOI: 10.1111/febs.15585
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and roles of β‐TrCP1/2 in carcinogenesis

Abstract: b-transducin repeat-containing protein (b-TrCP), one of the well-characterized F-box proteins, acts as a substrate receptor and constitutes an active SCF b-TrCP E3 ligase with a scaffold protein CUL1, a RING protein RBX1, and an adaptor protein SKP1. b-TrCP plays a critical role in the regulation of various physiological and pathological processes, including signal transduction, cell cycle progression, cell migration, DNA damage response, and tumorigenesis, by governing burgeoning amounts of key regulators for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 165 publications
0
36
0
Order By: Relevance
“…β-TrCP acts as a substrate receptor and constitutes an active SCF β-TrCP ligase with a scaffold protein cullin 1 (CUL1), a RING protein RBX1 and an adaptor protein SKP1 (37). β-TrCP plays a critical role in the regulation of various physiological and pathological processes, including signal transduction, cell cycle progression, cell migration, DNA damage response and tumorigenesis, by governing large amounts of key regulators for ubiquitination and proteasomal degradation (38). The results of previous studies have demonstrated that β-TrCP plays a vital role in carcinogenesis via promoting the degradation of its substrates, including oncoproteins and tumor suppressors (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-TrCP acts as a substrate receptor and constitutes an active SCF β-TrCP ligase with a scaffold protein cullin 1 (CUL1), a RING protein RBX1 and an adaptor protein SKP1 (37). β-TrCP plays a critical role in the regulation of various physiological and pathological processes, including signal transduction, cell cycle progression, cell migration, DNA damage response and tumorigenesis, by governing large amounts of key regulators for ubiquitination and proteasomal degradation (38). The results of previous studies have demonstrated that β-TrCP plays a vital role in carcinogenesis via promoting the degradation of its substrates, including oncoproteins and tumor suppressors (38).…”
Section: Discussionmentioning
confidence: 99%
“…β-TrCP plays a critical role in the regulation of various physiological and pathological processes, including signal transduction, cell cycle progression, cell migration, DNA damage response and tumorigenesis, by governing large amounts of key regulators for ubiquitination and proteasomal degradation (38). The results of previous studies have demonstrated that β-TrCP plays a vital role in carcinogenesis via promoting the degradation of its substrates, including oncoproteins and tumor suppressors (38). Specifically, the results of previous studies demonstrated that β-TrCP is upregulated in liver cancer tissues (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…β-TrcP2, also known as FBXW11, has been characterized to take part in tumorigenesis ( 36 ). FBXW11 activated the β-catenin/TCF and NF-kappa B pathways and increased cell proliferation in lymphocytic leukemia ( 37 ).…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%
“…In addition, the inhibition of β-TrCP can enhance the antiproliferative effect of antitumor drugs on breast cancer cells, thus inhibiting NF-κB activity [ 218 ]. Although the β-TrCP E3 ligase plays a key role in regulating immune response [ 219 ], the mechanism of β-TrCP inhibitors in tumor immunity remains unclear. Therefore, future studies should analyze the regulation of targeted β-TrCP in tumor immunity.…”
Section: Therapeutic Targeting Of E3 Ligases In Cancer Immunotherapymentioning
confidence: 99%